2005
DOI: 10.1111/j.1439-0426.2005.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

The recent distribution and abundance of non-native Neogobius fishes in the Slovak section of the River Danube

Abstract: The distributions of invasive Neogobius species were investigated in the Slovak section of the River Danube from Bratislava downstream to the village of Chl'aba. During October 2004, the main channel of the Danube was sampled, including by-pass, head-race and tail-race canals of the Gabcˇı´kovo dam, backwaters and the lower-most sections of the tributaries Maly´Dunaj, Hron, Va´h and IpelÕ. Three Neogobius species already documented in Slovakia were captured (monkey goby Neogobius fluviatilis, bighead goby N. k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 12 publications
1
82
0
3
Order By: Relevance
“…2). Our laboratory observations have shown that racer goby do constitute a real threat for bullhead, providing direct experimental evidence to the hypothesis that the decline of bullhead in European waters could be partially attributed to the recent invasions of the invasive Ponto-Caspian gobiids (Jurajda et al 2005; Dorenbosch and van der Velde 2009) due to direct competitive and aggressive interactions for space and food resources. Because both species studied are benthic clingers that use similar microhabitats (Brylinska 2000; Pinchuk et al 2003a, b) and their distributions may overlap (T. Kakareko, pers.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…2). Our laboratory observations have shown that racer goby do constitute a real threat for bullhead, providing direct experimental evidence to the hypothesis that the decline of bullhead in European waters could be partially attributed to the recent invasions of the invasive Ponto-Caspian gobiids (Jurajda et al 2005; Dorenbosch and van der Velde 2009) due to direct competitive and aggressive interactions for space and food resources. Because both species studied are benthic clingers that use similar microhabitats (Brylinska 2000; Pinchuk et al 2003a, b) and their distributions may overlap (T. Kakareko, pers.…”
Section: Discussionmentioning
confidence: 80%
“…The threat of Ponto-Caspian gobies to native Cottidae has already been demonstrated in the Laurentian Great Lakes, where invasive round goby have been found to out-compete native mottled sculpin Cottus bairdii for preferred habitat and to disrupt their reproduction (Dubs and Corkum 1996;Janssen and Jude 2001). Reported declines in European bullhead populations, coinciding with goby invasions of the rivers Danube (Jurajda et al 2005) and Rhine (Dorenbosch and van der Velde 2009) suggest that Ponto-Caspian gobies are having a similar adverse impact on European as on North American Cottidae. However, studies on the potential impacts of gobies on European bullhead (henceforth simply 'bullhead') are limited to one experimental study (van Kessel et al 2011), which focused on the potential displacement of bullhead and stone loach Barbatula barbatula from their preferred habitats by four gobiid species.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other studies have since monitored the species' expansion upstream beyond Slovakia and Austria (e.g. Ahnelt et al, 1998;Harka and Jakab, 2001;Holčik et al, 2003;Jurajda et al, 2005). The species reached Germany (Passau) in 1985, and was recorded 100 km upstream at Regensburg just a few years later (Reinartz et al, 2000).…”
Section: > Western Tubenose Goby Proterorhinus Semilunaris (Heckel 1mentioning
confidence: 99%
“…The next phenotypic character values were determined concerning the body: body weight (BW), total length (TL) [13], standard length (SL) [14], maximum height (H) [15], minimum height (h) [16], great perimeter (GP), small perimeter (SP) and body depth (BD). The last characters, as well as the body weight are not represented graphically.…”
Section: Methodsmentioning
confidence: 99%
“…The first racer goby specimen was caught in the same year, in October, from a Danube armlet near Bratislava (Kautman et al, 2001). In later studies conducted on the Slovak Danube, the species was no longer found and it was presumed that few local populations exist, thus the establishment process of this species in the middle Danube basin is at an initial phase (Jurajda et al, 2005). It appeared in Vistula River in Poland, in 2001 (Kostrzewa and Grabowski, 2001), the hypothesis according to which the species reaches the Baltic Sea basin from the Black Sea basin by the Bug-Pripyat Canal, which connects the two basins, was launched.…”
Section: Introductionmentioning
confidence: 99%